Vertical Profiling of Aerosol Physicochemical Properties With a New Airborne Aerosol Sampling System for Unmanned Aerial Vehicles and Tethered Balloons - Zhu, Shaowen; Ma, Nan; Yu, Pengfei; Xie, Linhong; Hong, Juan; Lu, Nan; Bai, Zhixuan; Deng, Zhaoze; Ran, Liang; Wu, Yunfei; Bian, Jianchun; Wang, Qiyuan; et al. (Journal of geophysical research. Atmospheres, 2025)
Vertical profiling of aerosol physicochemical properties, such as chemical composition, aerosol hygroscopicity, mixing state, is crucial for understanding their interactions with boundary layer evolution and their impacts on atmospheric environment. Traditional in situ vertical observations of those properties mainly rely on aircraft platforms, which are costly, subject to numerous constraints, and are unsuitable for near‐ground (<500 m) measurements. Unmanned aerial vehicles (UAVs) and tethered balloons (TBs) are ideal platforms for observations within the atmospheric boundary layer but can only carry portable instruments due to payload limitations. In this study, a novel method for vertical profiling of aerosol physicochemical properties within 1 km is designed utilizing a self‐developed lightweight airborne aerosol sampling system (AS2) integrated onto UAVs or TBs platforms. AS2 collects and preserves atmospheric aerosol samples in aerosol form, enabling subsequent analysis by online instruments at the ground station. During a field campaign in Golmud, Qinghai‐Tibet Plateau, in 2021, the AS2 was applied alongside a Single Particle Soot Photometer and a Humidified Tandem Differential Mobility Analyzer to obtain vertical profiles of the refractory black carbon (rBC) mixing state and aerosol hygroscopicity. Results show that both the rBC mixing state and aerosol hygroscopicity exhibit significant vertical and diurnal variations. Our method provides an easy‐to‐implement and cost‐effective approach for obtaining vertical distribution data on aerosol physicochemical properties, thereby aiding the expansion of relevant databases across various environments. Plain Language Summary Vertical distribution of aerosol physicochemical properties is essential for understanding their environment and climate effects. Traditional aircraft‐based measurements of those properties are costly and limited for near‐ground (<500 m) measurements. Unmanned aerial vehicles (UAVs) and tethered balloons (TBs), though optimal for near‐ground observations, are subject to payload constraints. This study introduces a new method for profiling these properties by developing a lightweight airborne aerosol sampling system (AS2) that can be attached to UAV or TB platforms. This system can collect and store atmospheric aerosol samples at different heights, enabling further analysis by online instruments at the ground station. During a 2021 field campaign in Golmud, AS2 was practically applied together with a Single Particle Soot Photometer and a Humidified Tandem Differential Mobility Analyzer to obtain the vertical profiles of refractory black carbon (rBC) mixing state and aerosol hygroscopicity. Results show that both rBC mixing state and aerosol hygroscopicity exhibit distinct vertical and diurnal variations, plausibly attributed to the effects of boundary layer evolution. Our method offers an easy‐to‐implement and cost‐effective way to obtain the vertical distribution of aerosol physicochemical properties across various environments. Key Points A novel method based on unmanned aerial vehicle and tethered balloon was designed for vertical profiling of aerosol physicochemical properties up to 1 km Significant vertical and diurnal variations in both rBC mixing state and aerosol hygroscopicity were observed during the campaign in Golmud